Scaled mass index derived from aerial photogrammetry associated with predicted metabolic pathway disruptions in free-ranging St. Lawrence Estuary belugas - Sherrill, Meredith; Bernier-Graveline, Alexandre; Ewald, Jessica; Pang, Zhiqiang; Moisan, Michel; Marzelière, Mathieu; Muzzy, Maris; Romano, Tracy A.; Michaud, Robert; Verreault, Jonathan (Frontiers in Marine Science, 2024)
The St. Lawrence Estuary (SLE) belugas (Quebec, Canada) are an endangered population whose numbers remain low despite ongoing conservation efforts. Multiple anthropogenic factors and changing environmental conditions are thought to have contributed to the recent 20-year decline in blubber fatty acid concentrations reported in stranded SLE belugas. Despite this evidence that energy reserves within the population are declining, there is currently no method for estimating the body condition of free-ranging animals. The potential metabolic consequences of declining fat reserves have also yet to be explored. The objectives of this study were to use unmanned aerial vehicle (UAV)-based photogrammetry to estimate the scaled mass index (SMI) of free-ranging SLE belugas, and to compare this proxy of body condition to the lipidome of outer-layer blubber samples collected from the same individuals via remote biopsy darting. Morphometric analysis of aerial images (n = 44 SLE belugas), combined with data collected from animals under professional human care, produced SMI estimates (females: 807 ± 98 kg, males: 743 ± 39 kg) similar in range to those previously calculated for SLE beluga carcasses of known weight. A non-targeted lipidomic analysis followed by pathway enrichment analysis, identified metabolic pathways predicted to show altered activity in association with SMI in the blubber of free-ranging male SLE belugas (n = 27). Mapping of enriched pathways compared to the Kyoto Encyclopedia of Genes and Genomes (KEGG) metabolic pathways maps, revealed that enriched pathways pertained to the metabolism of multiple lipid classes including fatty acyls and glycerophospholipids. Vitamin A, Vitamin E, and tyrosine metabolism pathways were also enriched in correlation with SMI. This study provides the basis for the development of a non-invasive technique for estimating the body condition of free-ranging SLE belugas and identifies metabolic pathways that merit further exploration to improve our understanding of the potential metabolic impacts of energy loss in cetaceans.